Hubungan antara Pola Asuh Orang Tua terhadap Sikap Bullying pada Remaja - Amalia Syahzidah; Siti Ina Savira (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Bullying behavior is not a new phenomenon, but has been happening in Indonesia for a long time and continues to increase. Bullying behavior is mentioned as a form of negative action based on the misuse of power and strength that is carried out intentionally and repeatedly by one or a group of students who are offensive. This study aims to determine the relationship between parenting patterns with bullying attitudes in adolescents. This study used a correlational study method with Accidental Sampling sampling technique which obtained the research subjects as many as 132 teenagers.. The data analysis technique used in this research is descriptive analysis and inferential analysis. The results of this study indicate a significant relationship between parenting and bullying attitudes in adolescents based on a sig value that is less than 0.05, which is 0.039. This study also shows the Correlation Coefficient value of -0.216 (rcount > 0.1946), meaning that there is a low and opposite correlation between parenting and bullying attitudes. This value also means that the higher the parenting style, the lower the bullying attitude in adolescents. The results of this study indicate that the highest dimension is found in the bully dimension which indicates that the bullying attitude of adolescents is mostly shown through the bullying behavior that has been carried out by the teenager. The results in this study also stated that the parenting pattern that was widely applied by the respondent's parents was permissive parenting. Parenting styles play different roles in child development adequately and depend on children's involvement in bullying behavior.